BLOOM OF TRICHODESMIUM THIEBAUTII GOMONT IN THE GULF OF MANNAR AT MANDAPAM - James, P S B R (Indian Journal of Fisheries, 2011)
A bloom of the blue-green alga, Trichodesmium thiebautii, was observedduring the last week of May 1968 in the Gulf of Mannar along the MandapamCoast. The alga was found in abundance in various stages of disintegrationin the glass tanks of the sea-water aquarium of the Central Marine FisheriesResearch Institute, Mandapam Camp, which caused mortality of fishes kept forexperimental purposes. However, no fish mortality was reported from the sea